Pharmacotherapy for Pulmonary Hypertension in Infants with Bronchopulmonary Dysplasia: Past, Present, and Future - Candice D. Fike; Judy L. Aschner (MDPI AG, 2023)
Approximately 8-42% of premature infants with chronic lung disease of prematurity, bronchopulmonary dysplasia (BPD), develop pulmonary hypertension (PH). Infants with BPD-PH carry alarmingly high mortality rates of up to 47%. Effective PH-targeted pharmacotherapies are desperately needed for these infants. Although many PH-targeted pharmacotherapies are commonly used to treat BPD-PH, all current use is off-label. Moreover, all current recommendations for the use of any PH-targeted therapy in infants with BPD-PH are based on expert opinion and consensus statements. Randomized Control Trials (RCTs) are needed to determine the efficacy of PH-targeted treatments in premature infants with or at risk of BPD-PH. Prior to performing efficacy RCTs, studies need to be conducted to obtain pharmacokinetic, pharmacodynamic, and safety data for any pharmacotherapy used in this understudied and fragile patient population. This review will discuss current and needed treatment strategies, identify knowledge deficits, and delineate both challenges to be overcome and approaches to be taken to develop effective PH-targeted pharmacotherapies that will improve outcomes for premature infants with or at risk of developing BPD-PH.